Issues of Translation from Russian to Hungarian and from Hungarian to Russian: Studia Litteraria 2020/1-2, LIX. évfolyam. Orosz irodalom fordításokban. Debrecen 2020, 146 p. HU ISSN 0562-2867 - Varga, Zsófia (Slavica, 2023)
This review is a content overview of the issue 1-2/2020 of Studia Litteraria, a Journal of Literary and Cultural Studies. This collection of scholarly articles is an excellent material for a varied and comprehensive look at current matters of translation and contemporary literature. The authors of the articles are practicing translators, therefore the general positions are explained through their own, specific works and practical experience. The purpose of this review is to briefly acquaint readers with the content of scholarly papers which have been categorized by topics for convenience.